The intricate role of Sir2 in oxidative stress response during the post-diauxic phase in Saccharomyces cerevisiae - Kim, Yeong Hyeock; Ryu, Ji-In; Devare, Mayur Nimbadas; Jung, Juhye; Kim, Jeong-Yoon (Frontiers in Microbiology, 2023)
Silent information regulator 2 (Sir2) is a conserved NAD+-dependent histone deacetylase crucial for regulating cellular stress response and the aging process in Saccharomyces cerevisiae. In this study, we investigated the molecular mechanism underlying how the absence of Sir2 can lead to altered stress susceptibilities in S. cerevisiae under different environmental and physiological conditions. In a glucose-complex medium, the sir2Δ strain showed increased sensitivity to H2O2 compared to the wild-type strain during the post-diauxic phase. In contrast, it displayed increased resistance during the exponential growth phase. Transcriptome analysis of yeast cells in the post-diauxic phase indicated that the sir2Δ mutant expressed several oxidative defense genes at lower levels than the wild-type, potentially accounting for its increased susceptibility to H2O2. Interestingly, however, the sir2Δras2Δ double mutant exhibited greater resistance to H2O2 than the ras2Δ single mutant counterpart. We found that the expression regulation of the cytoplasmic catalase encoded by CTT1 was critical for the increased resistance to H2O2 in the sir2Δras2Δ strain. The expression of the CTT1 gene was influenced by the combined effect of RAS2 deletion and the transcription factor Azf1, whose level was modulated by Sir2. These findings provide insights into the importance of understanding the intricate interactions among various factors contributing to cellular stress response.